Palmyra: the Centre of Textile Production and Trade? - Żuchowska, Marta (Anabasis. Studia Classica et Orientalia, 2022)
Palmyra, located in the heart of the Syrian desert is well known as a centre of caravan trade during the Roman Period. Although the involvement of the city in the long-distance trade was raised by many scholars, to date, very little research has been focused on the Palmyrene economy and its relation to the merchants’ activity. The only category of archaeological finds from Palmyra confirming its involvement in long-distance trade is textiles, abundant enough to allow for analysis of the directions of trade and its scope. At the same time, textiles and their representations in the Palmyrene iconography and textile tools found on the site constitute relevant evidence of the local textile industry and its relation with the regional and long-distance trade. This paper aims to analyse the Palmyrene textile industry and trade to understand Palmyra’s role in the complex network of production and exchange in Asia in the early 1st millennium AD.